2020
DOI: 10.2147/jbm.s232562
|View full text |Cite
|
Sign up to set email alerts
|

<p>The Effect of Serum Ferritin Level on Gonadal, Prolactin, Thyroid Hormones, and Thyroid Stimulating Hormone in Adult Males with Sickle Cell Anemia</p>

Abstract: Background: Sickle cell anaemia (SCA) is an inherited hemoglobinopathy resulting in sickling of erythrocytes that cause micro-vascular obstruction leading to acute complications and chronic organ damage. Adults with SCA have endocrine complications and metabolic alterations. The aim of this study was to assess the association between gonadal and thyroid hormones with iron indices and to explore the potential association between serum ferritin levels and sex hormones in adult males with sickle cell disease in N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 10 publications
(14 reference statements)
0
3
0
Order By: Relevance
“…Some previous research supports our findings, suggesting that high ferritin levels during puberty, particularly in thalassemia patients, are a risk factor for hypogonadotropic hypogonadism [ 50 ]. However, another cross-sectional study involving only 80 males with sickle cell anemia found that individuals in the high ferritin group had higher LH and lower testosterone in comparison to males in the normal ferritin group [ 51 ]. While we reported no association between ferritin and TT in infertile males, Liu et al found a significant association between ferritin concentrations and TT after adjusting for age and alcohol consumption amongst healthy men [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some previous research supports our findings, suggesting that high ferritin levels during puberty, particularly in thalassemia patients, are a risk factor for hypogonadotropic hypogonadism [ 50 ]. However, another cross-sectional study involving only 80 males with sickle cell anemia found that individuals in the high ferritin group had higher LH and lower testosterone in comparison to males in the normal ferritin group [ 51 ]. While we reported no association between ferritin and TT in infertile males, Liu et al found a significant association between ferritin concentrations and TT after adjusting for age and alcohol consumption amongst healthy men [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Demographics, injury and comorbidities, body composition, complications, and acute care are associated with the functional outcomes of hip fracture surgery (16); for example, age, male gender, inflammation, anemia, and infectious diseases foster multiple fracture hallmark functions, thus affecting patient survival. Sex hormones have been reported to be linked with inflammation, age, gender, and infectious diseases (15,17,18). However, the prognostic significance of sex hormones in older women undergoing hip fracture surgery remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with sickle cell anemia need testing for thyroid function because SCA results in sickling of erythrocytes that cause micro-vascular obstruction leading to acute complications and chronic organ damage, and endocrine glands are commonly affected. Thyroid disorders were frequently reported in patients with SCA [3]. Indications for screening for hypothyroidism are shown in Table 3 [3,7].…”
Section: Screening In Special Groupsmentioning
confidence: 99%
“…Thyroid disorders were frequently reported in patients with sickle cell anemia. So, these patients need frequent screening for serum ferritin level and hormonal assays including thyroid hormones [3].…”
Section: Introductionmentioning
confidence: 99%